2019
DOI: 10.1101/839142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting master transcription factors from pan-cancer expression data

Abstract: The function of critical developmental regulators can be subverted by cancer cells to control expression of oncogenic transcriptional programs. These "master transcription factors" (MTFs) are often essential for cancer cell survival and represent vulnerabilities that can be exploited therapeutically. The current approaches to identify candidate MTFs examine super-enhancer associated transcription factor-encoding genes with high connectivity in network models. This relies on chromatin immunoprecipitation-sequen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 91 publications
2
18
0
Order By: Relevance
“…At the protein level, PAX8 knockdown led to an almost complete disappearance of SOX17, and SOX17 knockdown led to a significant decrease in PAX8 levels. These results are reinforced by our recent findings showing that PAX8 and SOX17 were found to be master transcription factors that occupy regulatory elements related to their own encoding genes in ovarian cancer (39). Globally, PAX8 and SOX17 genomic binding sites co-localize within candidate active enhancers in HGSOC cell lines.…”
Section: Discussionsupporting
confidence: 63%
“…At the protein level, PAX8 knockdown led to an almost complete disappearance of SOX17, and SOX17 knockdown led to a significant decrease in PAX8 levels. These results are reinforced by our recent findings showing that PAX8 and SOX17 were found to be master transcription factors that occupy regulatory elements related to their own encoding genes in ovarian cancer (39). Globally, PAX8 and SOX17 genomic binding sites co-localize within candidate active enhancers in HGSOC cell lines.…”
Section: Discussionsupporting
confidence: 63%
“…KLF5 is also frequently amplified in gastric cancer (Chia et al, 2015; Zhang et al, 2018) and has recently been shown to regulate gene expression in OAC in combination with other transcription factors, GATA6, ELF3 and EHF (Chen et al, 2019). This was recently reinforced by a recent study that identified KLF5 as a master transcription factor on which OAC cell-lines were dependent (Reddy et al, 2019). Paradoxically, KLF5 has been shown to have a tumour suppressor role in oesophageal squamous cell carcinoma (Tarapore et al, 2013) and breast cancer (Chen et al, 2002).…”
Section: Discussionmentioning
confidence: 87%
“…Epithelial factors included SOX17, BARX2 and BHLHE41 in secretory epithelial cells, plus KLF5, TTF3 and RFX3 in ciliated epithelial cells. We recently identified SOX17 as a master regulator in high-grade serous ovarian cancers (Reddy et al, 2019), but SOX17 is not known to be a marker in physiologically normal fallopian tube epithelial cells. To validate this finding we performed immunohistochemistry for SOX17 on 14 fallopian tubes from cancer-free women; strong SOX17 staining was observed in all specimens, and was independent of age, menopausal status, and BRCA1/2 mutation status ( Figure 2B, Table S1).…”
Section: Single Cell Transcriptomic Analyses Of Normal Human Fallopiamentioning
confidence: 99%
“…Consistent with the RUNX3 regulon being specifically enriched in transitioning unclassified clusters 2 and 3, RUNX3 gene expression was unique to these clusters ( Figure 4D,F). TFs that characterize fallopian tube secretory epithelial cells are PAX8 (Levanon et al, 2010;Ozcan et al, 2011), SOX17 (this study and Reddy et al, 2019) and WT1, a clinically used biomarker of HGSC (Köbel et al, 2008;Shimizu et al, 2000). To understand the relationship of RUNX3 to these major secretory cell transcription factors, we transiently knocked down PAX8, SOX17 and WT1 in normal fallopian tube epithelial cells (FT282) and a HGSOC cell line (OVCAR4).…”
Section: Reconstructing Differentiation Trajectories In the Human Falmentioning
confidence: 99%
See 1 more Smart Citation